Effect of the ratio of graphene oxide(GO) and multi-walled carbon nanotubes(MWCNTs) on metal friction and wear during mixing. (February 2022) - Han, Deshang; Wang, Kongshuo; Yan, Gang; Pan, Yi; Xue, Junxiu; Wang, Chuansheng; Bian, Huiguang
Abstract: Internal mixer is an important mixing component in industrial applications. Studies show that when a mixer operates for a long time, wear may appear at the end face of the internal mixer. On the other hand, abrasion of the end face increases the gap between the mixing chamber and the end face. Then, leakage occurs, which reduces the mixing effect and affects the rubber performance. Therefore, it is of significant importance to study the wear of the end face during the mixing process. Graphene oxide (GO) and multi-walled carbon nanotubes (MWCNTs) have excellent electrical characteristics and thermal conductivity so that they have been widely used in various fields such as synthesized composite rubbers. GO and MWCNTs are mechanically blended into natural rubber to obtain GO/MWCNTs composite material. In the present study, the influence of the GO/MWCNTs ratio on the friction and wear of the end face of the internal mixer is analyzed. The obtained results show that MWCNTs and GO molecules interact to form a three-dimensional network structure, which has a greater impact on the degree of silica dispersion, silanization reaction, and metal wear. As the GO content increases, the average friction coefficient between rubber and metal, metal roughness, the proportion of abrasive wear, and the amount of metal wear gradually decrease. The lowest values can be achieved when the amount of added GO is set to 3 phr. When the GO in the mixture exceeds 3 phr, the friction coefficient between rubber and metal, and the metal roughness change, thereby affecting the proportion of abrasive wear and increasing the amount of metal wear in the mixing process. In this experiment, the amount of CNT that reduces GO aggregation is 6 phr. On the whole, when the ratio of GO/MWCNTs is 3/6, the synergistic effect of MWCNTs and GO molecules is maximized, the area of the three-dimensional network structure of GO/MWCNTs is the largest, the dispersibility of SiO2 is the best, and the amount of wear of the composite material on the metal is the lowest. Highlights: In the present study, the influence of the GO/MWCNTs ratio on the friction and wear of the end face of the internal mixer is analyzed. The obtained results show that MWCNTs and GO molecules interact to form a three-dimensional network structure. It is concluded that the metal wear is minimized when the ratio of GO/MWCNTs in the GO/MWCNTs composite is set to 3/6.